Dosing antipsychotics in special populations of patients with schizophrenia: severe psychotic agitation, first psychotic episode and elderly patients. (12th December 2021) - Mouaffak, Fayçal; Ferreri, Florian; Bourgin-Duchesnay, Julie; Baloche, Emmanuelle; Blin, Olivier; Vandel, Pierre; Garay, Ricardo P.; Vidailhet, Pierre; Corruble, Emmanuelle; Llorca, Pierre-Michel
ABSTRACT: Antipsychotic (AP) dosing is well established in nonelderly patients with acute exacerbations of schizophrenia, but not in special populations.This review describes the AP dosing procedures that have been used in clinical studies for acute psychotic agitation, a first episode of psychosis (FEP), and elderly patients. AP dosing data was extracted from the databases of drug regulatory authorities, and from clinical studies available in the medical literature. In acute psychotic agitation, intramuscular and oral APs are frequently prescribed in higher doses than those that saturate D2 receptors. Supersaturating doses of APs should be avoided due to an increased risk of adverse effects. In FEP, many studies showed efficacy of low doses of APs. Studies with risperidone and haloperidol suggested a dose reduction of approximately one third. Titration with a lower starting dose is recommended in elderly patients, due to possible decreases in pharmacokinetic clearance, and due to the risk of concomitant diseases and drug interactions. Exposure to some APs has been associated with QTc prolongation and arrhythmias, and a small but significant increase in the risk of stroke and mortality with APs has been seen, particularly in older people with dementia-related psychosis.